La gestion professionnelle des émotions et l’approche prothétique : un nouveau travail prescrit pour soigner les déments - Michel Bigaouette (Perspectives Interdisciplinaires sur le Travail et la Santé)
Caregivers who work with dementia patients face some significant difficulties. Among other things, their tasks involve preventing aggressive and disruptive behaviour among their patients. The strategies they use to do this are one of the fundamental issues in their work activity, and include professional management of the emotions experienced by patients during care activities, as well as those experienced by the caregivers themselves.An ergonomist worked with caregivers in residential and long-term care centres, mainly in order to document the emotion-related strategies used by caregivers, but also to support employers, union authorities and employees in the centres as they implemented more efficient care and service organization models. The « prosthetic » approach is an example of the ergonomist’s contribution. This approach redefines the caregiver’s prescribed work, in order to satisfy the basic needs of dementia patients in a more effective way.